2020
DOI: 10.4236/ce.2020.118112
|View full text |Cite
|
Sign up to set email alerts
|

Research and Practice in Teaching of Analytical Chemistry Based on Duifene PAD Class and Formative Evaluation

Abstract: Objective: This paper constructs a joint teaching mode based on the Duifene PAD class and formative evaluation, which is applied in the teaching of Analytical Chemistry, and explores its teaching effect. Methods: We selected undergraduate students of Pharmacy in our university as teaching objects that were randomly divided into the control group and the experimental group. The experimental group was taught in the joint teaching mode based on Duifene PAD class and formative evaluation, while the control group w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…2) The big data can be mined systematically with teaching platforms such as Duifene, Moso Teach and Rain Classroom, which solves the bottleneck of lack of formative evaluation evidence (Liao, Li, Huang, Li, Huang, Huang, & Tang, 2020), establishing an assessment mode combining formative evaluation and final assessment, paying attention to improving teachers' teaching ability, and promoting the improvement of teaching and learning and talent training quality.…”
Section: Build a "Thick Foundation" Training Methods Driven By "Wisdom Fusion Of Theory And Reality"mentioning
confidence: 99%
“…2) The big data can be mined systematically with teaching platforms such as Duifene, Moso Teach and Rain Classroom, which solves the bottleneck of lack of formative evaluation evidence (Liao, Li, Huang, Li, Huang, Huang, & Tang, 2020), establishing an assessment mode combining formative evaluation and final assessment, paying attention to improving teachers' teaching ability, and promoting the improvement of teaching and learning and talent training quality.…”
Section: Build a "Thick Foundation" Training Methods Driven By "Wisdom Fusion Of Theory And Reality"mentioning
confidence: 99%
“…According to the survey, students believe that the PAD Class has significantly improved their lifelong learning ability (94.74%), independent learning ability (94.73%), ability in acquisition of information (94.73%), ability of information technology application (89.48%) and ability in acquisition of knowledge (89.47%), which indicates that the PAD Class gives full play to the subjective ability of students' learning. Previous research found that the PAD Class has a certain promotion effect on students' independent learning ability and other aspects (Liao, Li, Huang, Li, Huang, Huang, & Tang, 2020). During assimilation, students need to prepare materials for discussion.…”
Section: Pad Class Is Conducive To Promoting Students' Independent Learningmentioning
confidence: 99%
“…Through the questionnaire survey, optimize the index system, eliminate unreasonable items and add new indicators appropriately. The questionnaire was divided into two parts, the first part was a scoring scale, and the second part Secondary index Formulate a comprehensive curriculum ideological and political Timely adjust the teaching plan content rich and informative The teaching content can reflect frontier The teaching Ideological and political Open or elective courses online teaching resources publish teaching related papers and monographs lecture information is reasonable and rich [17]. Satisfaction of each respondent with the scale according to Table 3, which is a scale of the overall satisfaction of the respondents.…”
Section: Satisfaction Questionnaire Designmentioning
confidence: 99%